The Cellular and Molecular Interaction Between Erythrocytes and Plasmodium falciparum Merozoites - Molina-Franky, Jessica; Patarroyo, Manuel Elkin; Kalkum, Markus; Patarroyo, Manuel Alfonso (Frontiers in Cellular and Infection Microbiology, 2022)
Plasmodium falciparum is the most lethal human malaria parasite, partly due to its genetic variability and ability to use multiple invasion routes via its binding to host cell surface receptors. The parasite extensively modifies infected red blood cell architecture to promote its survival which leads to increased cell membrane rigidity, adhesiveness and permeability. Merozoites are initially released from infected hepatocytes and efficiently enter red blood cells in a well-orchestrated process that involves specific interactions between parasite ligands and erythrocyte receptors; symptoms of the disease occur during the life-cycle’s blood stage due to capillary blockage and massive erythrocyte lysis. Several studies have focused on elucidating molecular merozoite/erythrocyte interactions and host cell modifications; however, further in-depth analysis is required for understanding the parasite’s biology and thus provide the fundamental tools for developing prophylactic or therapeutic alternatives to mitigate or eliminate Plasmodium falciparum-related malaria. This review focuses on the cellular and molecular events during Plasmodium falciparum merozoite invasion of red blood cells and the alterations that occur in an erythrocyte once it has become infected.